1997
DOI: 10.1007/bf02247843
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of serum soluble intercellular adhesion molecule-1 (sICAM-1) and beta-2-microglobulin in Sjögren's syndrome

Abstract: Sjögren's syndrome is a chronic inflammatory disease which is believed to be immunologically mediated. It is marked by inflammation and destruction of the salivary glands and lacrimal glands. We have found significantly higher serum levels of sICAM-1 and beta-2-microglobulin in both primary Sjögren's syndrome patients (429.1 +/- 114.33 ng/ml, 4.4 +/- 1.5 ug/ml resp.) and secondary Sjögren's syndrome patients (424 +/- 140.73 ng/ml, 4.4 +/- 2.67 ug/ml resp.) in comparison with healthy controls (189.1 +/- 42.34 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The elevated levels of soluble adhesion molecules are found in the serum of patients with various inflammatory diseases and may provide some useful diagnostic or prognostic information (7). The serum or plasma levels of soluble forms of adhesion molecules are reported to be elevated in patients with various immunopathological diseases such as atopic dermatitis and psoriasis (6), vasculitis and scleroderma (5), Sj(gren syndrome (11,12), atherosclerosis (2,3), systemic lupus erythematosus (22) as well as in malignancies (1,23) and in infectious disorders such as septic shock (18).…”
Section: Discussionmentioning
confidence: 99%
“…The elevated levels of soluble adhesion molecules are found in the serum of patients with various inflammatory diseases and may provide some useful diagnostic or prognostic information (7). The serum or plasma levels of soluble forms of adhesion molecules are reported to be elevated in patients with various immunopathological diseases such as atopic dermatitis and psoriasis (6), vasculitis and scleroderma (5), Sj(gren syndrome (11,12), atherosclerosis (2,3), systemic lupus erythematosus (22) as well as in malignancies (1,23) and in infectious disorders such as septic shock (18).…”
Section: Discussionmentioning
confidence: 99%
“…Another evidence of lymphoproliferation in lung tissue comes from elevated beta-2-microglobulin that is released by lymphocytic tissue and elevated in serum from patients with pSS, particularly pulmonary pSS (58, 59). Lahdensuo and Korpela prospectively studied seventeen patients with pSS with no history of smoking to evaluate the correlation between pulmonary findings including chest CT and pulmonary function tests and serum beta-2-microglobulin as well as immunoglobulins including IgA, IgG, IgM.…”
Section: Pathogenesismentioning
confidence: 99%
“…Johanssen et al (18) found hig- her levels of ICAM-1 in both serum and residual saliva of patients with primary SS in comparison with control. Recently, we have reported that serum levels of ICAM-1 is significantly higher in primary and secondary SS patients and in the case of secondary SS the level of sICAM-1 is correlated with the level of beta-2 microglobulin (20).…”
Section: Discussionmentioning
confidence: 91%